2017
DOI: 10.3389/fpls.2017.01820
|View full text |Cite
|
Sign up to set email alerts
|

Non-replicative Integral Membrane Proteins Encoded by Plant Alpha-Like Viruses: Emergence of Diverse Orphan ORFs and Movement Protein Genes

Abstract: Fast accumulation of sequencing data on plant virus genomes and plant transcriptomes demands periodic re-evaluation of current views on the genome evolution of viruses. Here, we substantiate and further detail our previously mostly speculative model on the origin and evolution of triple gene block (TGB) encoding plant virus movement proteins TGB1, TGB2, and TGB3. Recent experimental data on functional competence of transport gene modules consisting of two proteins related to TGB1 and TGB2, as well as sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…CsVX is rather inefficiently transmitted to Nicotiana benthamiana , whereas CsNAV causes no infection of this plant host [130] . These data support our earlier hypothesis [129] , [131] , [132] that a TGB3-related gene could be an accessory, rather than essential, TGB component, which can be necessary in certain hosts species or plant tissues at least in potexviruses [133] , [134] .…”
Section: Triple Gene Blocksupporting
confidence: 90%
See 1 more Smart Citation
“…CsVX is rather inefficiently transmitted to Nicotiana benthamiana , whereas CsNAV causes no infection of this plant host [130] . These data support our earlier hypothesis [129] , [131] , [132] that a TGB3-related gene could be an accessory, rather than essential, TGB component, which can be necessary in certain hosts species or plant tissues at least in potexviruses [133] , [134] .…”
Section: Triple Gene Blocksupporting
confidence: 90%
“…TGB3 proteins form two distinct groups, potex-like and hordei-like TGBs, depending on the presence of a single (genera Potexvirus , Carlavirus , Foveavirus and Allexivirus ) or two (genera Hordeivirus , Pomovirus , Goravirus and Pecluvirus ) TMDs ( Tables S2 and S3 ). Recently, we have revealed two additional TGB classes, one of which combines TGBs of several related viruses belonging to the genus Benyvirus (see below), whereas another one is represented by the TGB of virus-like RNA assembly in the transcriptome of Colobanthus quitensis (Cq-VLRA) resembling a plant virus genome fragment encoding proteins distantly related to the respective proteins of the genus Benyvirus [131] , [132] ( Table S4 ). Like the hordei-like TGB3 proteins, the benyvirus TGB3 has two transmembrane domains; however, the benyvirus TGB3 protein differs from hordei-like proteins by the location of N-terminal transmembrane domain very close to the protein terminus and a conserved sequence signature found only in the genus Benyvirus [52] , [131] , [132] , [135] ( Table S4 ).…”
Section: Triple Gene Blockmentioning
confidence: 99%
“…The ML phylogenetic tree, based on RdRp sequences encoded by the RNA1 segments, showed that WhIV-21 is clustered with a bee pathogen, Chronic bee paralysis virus (CBPV, proposed genus "Chroparavirus"), and several invertebrate tombus-like viruses (Shi et al, 2016a;Bigot et al, 2017; Supplementary Figure S7D). Similar to CBPV, which may form a ellipsoidal virion, the WhIV-21 RNA2 segment seems to encode two proteins; a putative virion glycoprotein and SP24 homolog that probably have features of the major structural components, similar to what was previously proposed for CBPV and some negeviruses (Kuchibhatla et al, 2014;Solovyev and Morozov, 2017).…”
Section: Characterization Of Tombus-like Virus Sequencessupporting
confidence: 56%
“…In the case of contigs BaA1_c637 (1,390 reads) and BaA1_c28720 (210 reads), an attempt to connect their sequences using RT-PCR failed, possibly because of a very low level of virus titer in the samples (data not shown). These two newly assembled contigs derived from four above-mentioned virus-like sequences have large replicase-like ORFs (ORF1) followed by two putative structural protein genes for predicted glycoprotein and membrane protein SP24 (ORFs 2 and 3) (Kuchibhatla et al, 2014;Solovyev and Morozov, 2017), except for the BaA1_c12 contig, which has an additional small ORF in its 3 -proximal region, or the BaA1_c14/63 contig, which lacks the 3 -terminal region sequence (Shi et al, 2016a; Figure 2 and Supplementary Figures S3, S4). The nucleotide sequence and encoded proteins of BaA1_c12 are almost identical (>99% nucleotide and 99-100% amino .…”
Section: Characterization Of Nege/kita-like Virus Sequencesmentioning
confidence: 99%
“…The shaping of current cilevirus genomes might have undergone the action of evolutionary forces biased not only by their plant hosts but also by their vectors. Horizontal gene transfer among viruses, or even between viruses and plants, has been suggested as a suitable mechanism for the acquisitions of new genes by plant virus genomes, as properly explained in the case of the binary movement block genes of the kitavirus hibiscus green spot virus 2 (Solovyev and Morozov, 2017). Moreover, blunerviruses and cileviruses encode a 30K MP displaying their best identities with those from virgavirids (Supplementary Figure S4) from which it could likely have been integrated by recombination (Quito-Avila et al, 2013).…”
Section: Discussionmentioning
confidence: 98%